STUDI PROSES PENCIPTAAN KARYA MUSIK OLEH MAHASISWA PROGRAM STUDI SENI TARI DAN MUSIK - Rami Syahbandi; Aloysius Mering; Chiristianly Yery Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this study was to identify the process of creating musical composition by students of dance and music study programs in making works intended as a condition for obtaining a bachelor's degree. This research also identified and outlined the differences in the creation process that they went through in making musical composition. The researcher used qualitative research methods to look for traits, elements, and characters about a phenomenon that begins with collecting, analyzing, and interpreting data. The results of this study are that the process of creating musical composition, especially thesis music works carried out by students (composers) must go through several stages, starting from the excavation of ideas to the implementation of the work form. While the differences in the creation process are found in the creation theory used and the stages of the creation process chosen. Keywords: Dance and Music Study Program, Music, Process of Creation